Molecular analysis of Chinese truffles resembling Tuber californicum in morphology reveals a rich pattern of species diversity with emphasis on four new species. (1st March 2016) - Fan, Li; Han, Ling; Zhang, Peng-rui; Yan, Xiang-yuan
Abstract : In China the species name Tuber californicum is assigned to pale truffles in the genus Tuber that have more or less regularly globose ascospores; however, we recently discovered that the name was misapplied to some specimens collected in China. In the present study we re-examined all available Chinese collections purported to be T. californicum, including herbarium specimens and newly collected materials, with morphological and molecular methods. The accessions separated into seven clusters in a phylogenetic analysis based on sequences of the internal transcribed spacers sequences of these materials. An ML tree generated with ITS, nuc 28S rDNA and translation elongation factor-1α sequences from Chinese and worldwide Tuber species with globose ascospores showed only two clades, the Puberulum clade and Latisporum clade. The Latisporum clade as recognized in this study includes the species known from eastern Asia only and probably represents a new lineage that arose in parallel with the Puberulum, Maculatum and Gibbosum lineages. We concluded that no evidence supports the existence of T. californicum in China and that the specimens misidentified as T. californicum belong to four species newly described herein, T. xuanhuaense, T. jinshajiangense, T. caoi and T. parvomurphium .